2018
DOI: 10.3389/fimmu.2018.01259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Terrestrialization on the Skin Mucus Proteome of African Lungfish (Protopterus dolloi)

Abstract: Animal mucosal barriers constantly interact with the external environment, and this interaction is markedly different in aquatic and terrestrial environments. Transitioning from water to land was a critical step in vertebrate evolution, but the immune adaptations that mucosal barriers such as the skin underwent during that process are essentially unknown. Vertebrate animals such as the African lungfish have a bimodal life, switching from freshwater to terrestrial habitats when environmental conditions are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The skin is recognized as a secondary respiratory tissue in several species (Urbina and Meredith 2014), and in lungfish, epidermal mucus is directly related to respiratory physiology (Heimroth et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The skin is recognized as a secondary respiratory tissue in several species (Urbina and Meredith 2014), and in lungfish, epidermal mucus is directly related to respiratory physiology (Heimroth et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While we hypothesize that skin mucus from both cartilaginous fish and lobe-finned fish contains these compounds as well, it has not been as extensively explored as in teleost fish. Supporting this hypothesis are studies showing that a transcript for a lectin, pentraxin, was found in the skin mucus of the common skate ( Raja kenojei ), while AMPs, including histones and S100 proteins, were found in the skin mucus of the African Lungfish ( Protopterus dolloi ) (20, 22).…”
Section: Physical Barriersmentioning
confidence: 94%
“…The scales of cartilaginous fish are called placoid scales, also known as denticles (16). The skin of lobe-finned fish contains keratinocytes, granulocytes and B cells (20). Lobe-finned fish have cosmoid scales that includes a layer of dense, lamellar bone called isopedine.…”
Section: Physical Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that the "adult epidermal keratin genes" were not expressed in lungfish skin in underwater environments. Indeed, Heimroth et al (2018) reported that the epidermis of lungfish showed notable changes and became more compact with flattened keratinocytes in response to experimental terrestrial conditions. Therefore, it would be worthwhile to analyze the RNA-seq data collected from the skin of this terrestrial condition to examine the above possibility.…”
Section: Origin Of Keratin Genes Specific To Terrestrial Vertebratesmentioning
confidence: 99%